Breeding and lactation efficiencies and lifetime productivity of Jaffrabadi buffaloes - P.U. GAJBHIYE, M.R. GADARIYA, P.H. VATALIYA K.S. MURTHY, H.H. SAVSANI (Indian Journal of Animal Production and Management, 2019)
Breeding efficiency and lactation efficiency during the productive herd-life along with lifetime productivitybased on 863 calving of 149 Jaffrabadi buffaloes calved and performed during 1991 to 2010 at CattleBreeding Farm, JAU, Junagadh were studied. Productive life, lifetime total milk production (LTMP) andmaximum standard lactation Yield (MSLMY) and association of breeding and lactation efficiencies withproduction traits were also investigated. The age at first calving (AFC) and over-all calving interval (CI)of Jaffrabadi buffaloes were, 1656.68±28.57 days (54.3months) and 541.94±7.88 days (17.8 months),respectively. Calving interval ranged between from 532 to 558 among different lactations, the parityeffect being non-significant. In general, it increased from 1st to 4th lactation. Then after the trend was notdefinite. The breeding efficiency as per Wilcox (BE-W) of the Jaffrabadi buffaloes based on all calvingsduring life time averaged 74.69±2.47%. When AFC was also taken into account, breeding efficiency ofthe buffaloes as per Tomar (BE-T) was estimated to be 79.04±1.46 %. About 28 % of heifers calved forthe first time below the average age of 47 months and 31 % of buffaloes calved at an average calvinginterval of 15 months. Lactation period of Jaffrabadi buffaloes varied from 247.50 to 335.69 days, over-allaverage being 291.87±4.96 days. The parity effect was significant (p